Study on the Migration Mechanism of Temporary Plugging Agent in Artificial Fractures of Deep Geothermal Reservoirs Based on the Euler-Euler Multiphase Flow Model - Yang, Zirui; Wang, Daobing; Li, Zongze; Wu, Yue; Yu, Bo (Journal of Advanced Thermal Science Research, 2024)
The successful use of temporary plugging diverting fracturing technology requires an understanding of the migration and plugging processes of temporary plugging agents into artificial fractures under high temperature settings. In this study, a multiphase flow model for the migration of temporary plugging agents in artificial fractures was developed using the Euler-Euler framework, and numerical simulations were conducted at elevated temperatures. Various factors, including plugging agent injection velocity, concentration, carrying fluid viscosity, wall temperature, and fracture width, were systematically analyzed to assess their impact on the agent’s migration behavior. Detailed analyses, using cloud diagrams of particle volume fraction, velocity, and turbulence intensity, clarified the underlying mechanisms influencing the migration process. The results indicate that as the injection velocity increases, the height of blockages near the wellbore decreases, while the blockage length initially increases before declining. Increasing the concentration of the plugging agent leads to a rise in blockage height and a shift in the front edge toward the injection point. Enhancing the viscosity of the carrying fluid enables the plugging agent to migrate deeper into the fracture, improving deep plugging effectiveness. While changes in wall temperature have limited impact on blockage morphology, temperatures exceeding the critical threshold of 573K significantly intensify particle migration. Moreover, increasing fracture width enhances both the height and length of blockages, with the optimal plugging effect observed when the plugging agent diameter is approximately one-third of the fracture width.